Nearly lattice-matched molybdenum disulfide/gallium nitride heterostructure enabling high-performance phototransistors - Liu, Xinke; Chen, Yuxuan; Li, Dabing; Wang, Sheng-Wen; Ting, Chao-Cheng; Chen, Lin; Ang, Kah-Wee; Qiu, Cheng-Wei; Chueh, Yu-Lun; Sun, Xiaojuan; Kuo, Hao-Chung (My University, 2019)
Molybdenum disulfide (MoS2)-based phototransistors are attractive for optical electronics in a large-scale size, such as transparent touch screens. However, most of the work done over the past decade has been on an opaque SiO2/Si wafer with a small size (micrometer to millimeter). In this work, a large-scale multilayer MoS2-based phototransistor has been fabricated on a transparent freestanding gallium nitride (GaN) wafer using a scalable chemical vapor deposition method. Due to the near lattice match and small thermal expansion mismatch between GaN and MoS2, the as-grown multilayer MoS2-on-GaN film shows high material quality in terms of low full width at half-maximum (similar to 5.16 cm(-1)) for the E-2g(1) Raman mode and a high absorption coefficient (similar to 10(6) cm(-1)) in the wavelength range of 405-638 nm. Under a wavelength of 405 nm at an incident power of 2 mWand applied voltage of 9 V, the fabricated MoS2-on-GaN phototransistor achieved a maximum responsivity of 17.2 A/W, a photocurrent gain of 53.6, and an external quantum efficiency of 5289%, with specific detectivity (similar to 10(10)-10(12) Jones) and low noise equivalent power (10(-12)-10(-14) W/Hz(1/2)) in the visible range of 405-638 nm. A typical response time of 0.1-4 s in the ambient air has also been recorded for the demonstrated MoS2-on-GaN phototransistor. Our work paves a technologic stepping stone for MoS2-based phototransistors for multifunctional transparent and touch-based optoelectronics in the future. (C) 2019 Chinese Laser Press